The Expectations Regarding Aging and Ageism Perspective between Nurses and Caregivers in Long-term Care Facilities - Dianis Wulan Sari; Elida Ulfiana; Nourmayansa Vidya Anggraini; Niko Dima Kristianingrum; Gading Ekapuja Aurizki; Maiko Noguchi-Watanabe (Nurse Media: Journal of Nursing)
Background:  Ageism negatively impacts older adults’ health, especially in long-term care facilities (LTCFs), where healthcare workers often hold unfavorable views of them. Understanding these perspectives is vital for combating ageism and improving LTCF quality. Yet, comprehensive studies on healthcare workers’ attitudes toward ageism are lacking, hindering targeted interventions. Therefore, grasping their attitudes and behaviors is crucial for addressing ageism in LTCFs and enhancing care for older adults.